Pelatihan soft skill sebagai strategi eskalasi promosi UMKM di desa eko–eduwisata Kandri dan Jatirejo, Kecamatan Gunungpati, Kota Semarang - William Ben Gunawan; Monica Rachmani (Altruis: Journal of Community Services, 2022)
Jatirejo Village has the potential to become a tourist village because of its attraction as a Kolang-Kaling Processed Village (Kokolaka) and has a River Tubing Topongeli tour. On the other hand, Kandri Village also has tourist attractions such as Kreo Cave and Jatibarang Reservoir. The skill of making promotional media designs and compiling reports on business activities is important in a tourist village. Therefore, Diponegoro University students are interested in holding a service with the title "Strategy for Expanding MSME Market Share in Eko-Eduwisata Jatirejo Village and Gunungpati District Kandri through Strengthening Internal Quality." This activity was held from July – to August 2021 for 45 days. The service was carried out in Kandri Village and Jatirejo Village, which are located in Gunungpati District, Semarang City. The main result of this service activity is training to improve the soft skills of participants in making promotional designs, compiling financial reports, as well as several outputs such as Guidebooks and Typical Product Promotional Poster Designs. Based on the results of the implementationof activities, the partners have received training in making reports and designs based on Microsoft Excel, Microsoft Word, and Canva. The advice on the sustainability of the program is the empowerment of young people who are more capable of using devices for marketing design such as laptops and cameras. Economic capabilities and activities in Jatirejo and Kandri MSMEs are expected to increase, especially after the COVID-19 pandemic has passed.